Progress of analysis of dissociation of 10C, 10B and 12C nuclei in nuclear track emulsion - Artemenkov D. A.; Bradnova V.; Firu E.; Haiduc M.; Kattabekov R. R.; Kharlamov S. P.; Kornegrutsa N. K.; Mamatkulov K. Z.; Neagu A.; Rukoyatkin P. A.; Rusakova V. V.; Stanoeva R.; et al. (EPJ Web of Conferences, 2017)
Recent findings related with the unstable nuclei 8Be and 9B in the coherent dissociation of relativistic nuclei 10C, 10B and 12C in nuclear track emulsion (“white”stars) are highlighted. Selection of the 10C “white”stars accompanied by 8Be (9B) leads to appearance of the distinct peak with a maximum at 4.1 ± 0.3 MeV in the excitation energy distribution of 2α2p ensembles. The 8Beg.s. nucleus is manifested in the coherent dissociation 10B → 2He + H with a probability of 25 ± 5 % including 13 ± 3 % of 9B decays. A probability ratio of the mirror channels 9B + n and 9Be + p is estimated to be 10 ± 1. Reanalysis of relativistic 12C dissociation in lead enriched emulsion revealed 9 3α-events corresponding to the Hoyle state.